Lis pendens in international litigation - McLachlan, Campbell; Hague Academy of International Law.
"A collection of law lectures in pocketbook form." "Full text of the lecture published in August 2009 in the Recueil des cours, Vol. 338 (2008)"--T.p.verso.
Introduction -- Private international litigation -- International arbitration -- Public international litigation -- Conclusion.
"Full text of the lecture published in August 2009 in the Recueil des cours, Vol. 338 (2008)"--T.p.verso.
Includes bibliographical references (pages 468-480).
Keywords: Lis pendens; Conflict of laws -- Arbitration and award; International commercial arbitration; Conflict of laws. -- Arbitration and award; International commercial arbitration